Impact of comorbid burden on global left cardiac function and prediction models for myocardial function damage: a cardiac magnetic resonance feature-tracking study - Qu, XiaoFeng; Bai, Miaomiao; Lyu, Jianbo; Yin, Lili; Zhang, Jiahui; Zhao, Endong; Mei, Lingjun (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the effects of comorbid burden on left cardiac myocardial function in patients without organic heart disease and to construct prediction models for myocardial function damage.MethodsA total of 82 healthy individuals and 198 patients with comorbid burden who had normal left ventricular ejection fraction (LVEF) were recruited. Comorbid burden included hypertension, type 2 diabetes mellitus (T2DM), and dyslipidemia. Based on the number of comorbidities, the patients were divided into two groups: comorbid burden <2 and comorbid burden ≥2. Cardiac magnetic resonance feature tracking (CMR-FT) was used to measure myocardial strain parameters.ResultsAfter adjustment, the left atrial (LA) reservoir strain (p = 0.011) and conduit strain (p < 0.001) were significantly lower in patients with a comorbid burden ≥2. The left ventricular (LV) global longitudinal strain (p < 0.001) and global radial strain (p = 0.010) were decreased in both the comorbid burden<2 and comorbid burden≥2 groups. The LV global circumferential strain (p = 0.006) was reduced in the comorbid burder≥2 group. Comorbid burden combined with male sex, postprandial blood glucose (PBG), and fasting blood glucose (FBG) proved to be excellent predictors of LV myocardial function damage (AUC = 0.848). In contrast, comorbid burden combined with male sex was only a fair predictor of LA myocardial function damage (AUC = 0.651).ConclusionCMR-FT can detect left-sided myocardial function damage in patients with comorbid burden but without organic heart disease prior to a decrease in LVEF. Comorbid burden combined with male sex, PBG, and FBG showed excellent predictive ability for LV myocardial function damage. Comorbid burden combined with the male sex showed a fair predictive ability for LA myocardial function damage.